(untitled) (SCIÉNDO INGENIUM, 2022)
The objective of this research work was to determine the effect of the internal control components as a measuring instrument on the efficiency and effectiveness of the treasury area of ​​the Provincial Municipality of Santa Period, 2017. The type of research used was descriptive, because the Data were observed, analyzed and described as shown, the research design used was non-experimental and with respect to temporality it was cross-sectional, because the variables were not manipulated, only the relationship between them was analyzed and described. The population and sample was made up of 100% of personnel from the Treasury Area of ​​the Provincial Municipality of Santa which had 16 workers, the instruments and data collection techniques used were observation and interview, as well as an analysis Documentary that includes monthly cash reports. For all this, it was possible to conclude that the components of internal control as a measurement instrument have a positive effect on the efficiency and effectiveness of the area of ​​the Provincial Municipality of Santa Period, 2017.